2005
DOI: 10.1074/mcp.m500062-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Lipolytic Proteome of Mouse Adipose Tissue

Abstract: In animals, plant seeds, and fungi, excessive amounts of lipids are stored in the form of intracellular triacylglycerol (TG) 1 and steryl ester deposits. Mammals store TG in adipose tissue as the primary source of energy during periods of starvation and increased energy demand. The balance of lipid storage and mobilization is tightly regulated to ensure whole body energy homeostasis. Stored fat is mobilized by activation of lipolytic enzymes, which degrade adipose TG and cholesterol esters and release non-este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…Although adipocyte lipolysis is regulated by a variety of proteins exhibiting lipase activity (Birner-Gruenberger et al, 2005), HSL plays an important role in this process and, together with ATGL, is responsible for more than 95% of lipase activity in murine white adipose tissue (Schweiger et al, 2006). A recent study from Zhou's group elegantly showed that chronic alcohol feeding was associated with increased ATGL expression and HSL activation in adipose tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Although adipocyte lipolysis is regulated by a variety of proteins exhibiting lipase activity (Birner-Gruenberger et al, 2005), HSL plays an important role in this process and, together with ATGL, is responsible for more than 95% of lipase activity in murine white adipose tissue (Schweiger et al, 2006). A recent study from Zhou's group elegantly showed that chronic alcohol feeding was associated with increased ATGL expression and HSL activation in adipose tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Others have subsequently confirmed the presence of triacylglycerol hydrolase (TGH; carboxylesterase 3; EC 3.1.1.1) in adipose tissue (10). TGH is a 60 kDa microsomal lipase that contains a catalytic triad with an active site serine located in the GXSXG motif (68).…”
Section: Triacylglycerol Hydrolasesmentioning
confidence: 99%
“…Abhydrolase domain-containing protein 11 is encoded on a chromosomal region that is often deleted in the human developmental disorder Williams-Beuren syndrome (38). Earlier experiments using substrates with various polarities led to the conclusion that this protein may rather be an esterase than a lipase (19). Enolase 1, which is also a serine hydrolase, catalyzes the stereochemically specific anti-elimination of water from 2-phosphoglycerate to form P-enolpyruvate in a stepwise reaction (39).…”
Section: Figmentioning
confidence: 99%
“…Expression in other tissues is rather low. Currently it cannot be excluded, that other lipases also exist that are important for lipid catabolism (19). Recent functional proteomic screens in various mouse tissues led to the identification of enzyme candidates that are currently subject to functional characterization (unpublished data).…”
mentioning
confidence: 99%